Development of Hanzi Radical Learning Media Xīnzìpáng for Students - Parmawati, Vitrianti Della; Pamuji, Dian Yuni; Marsuki, Ria Riski; Agwinanda , Almira (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2024)
This research was conducted based on the results of observations which showed that hanzi learning media for Chinese Language Education students at Semarang State University needed the development of creative and innovative hanzi learning media. The objectives of this research are 1) to describe the results of the needs analysis of radical hanzi learning media "忄xīn" for Chinese Language Education students at Semarang State University, 2) to describe the results of the prototype of radical hanzi learning media "忄xīn" for Mandarin Language Education students at Semarang State University, 3) to describe the results of expert validation of radical hanzi learning media "忄xīn" for Mandarin Language Education students at Semarang State University. The results of validation of learning media by material experts obtained an overall average score of 87, which was included in the score of 4. And the results of validation of learning media by media experts obtained an overall average score of 87.5, which was included in the score of 4 with the category very feasible to use with some improvements so that the media will be better and maximally used.